Characterization and Exploration of Applications of Nanocellulose Derived From Sargassum Muticum - Cody O'Brien (The Owl)
Sargassum muticum is an invasive species of marine algae affecting Florida and other areas along the Atlantic Ocean. There is urgency to find real-world applications of this species or its products, such as its cellulose nanofibers (CNFs) and nanocrystals (CNCs), collectively known as nanocellulose. The objective of this project was to attempt the first documented extraction of CNFs from S. muticum, perform tests and imaging on them, and explore their future applications in medicine, concrete reinforcement, insulation, and other fields. Nanocellulose acts as a more sustainable alternative to the standard materials used for those purposes, offering improved human and environmental health outcomes. The algae was dried, grinded, and bleached, and then refluxed in a sodium hydroxide solution to remove the proteins. Then, a chloroform-methanol-water solution was used to remove the algae's lipids and pigments. Finally, a hydrochloric acid solution was used to further refine the remaining carbohydrate-based cellulose. The sample was centrifuged between each refluxation. The final product was characterized using Fourier-transform infrared spectroscopy (FT-IR), X-ray diffractometry (XRD), and transmission electron microscopy (TEM), which confirmed the successful extraction of CNCs, contrary to original expectations. These CNCs, measuring between 70 and 700 nm in length and below 10 nm in width, compared favorably with CNCs from other sources, including other species of algae.